Pedagogical strategies for enhancing physical activity: A systematic review of trends and approaches - Marina Jagiello; Marc Lochbaum (Pedagogy of Health)
Background and purpose of the study. In modern society, issues of physical health and an active lifestyle are becoming increasingly relevant. However, despite the growing interest in this topic, there is a need for a more in-depth understanding of the pedagogical aspects of physical activity. The purpose of this study is to analyze academic publications on the pedagogical aspects of physical activity to identify current trends, issues, and prospects in this field.